Generation License: A Justified Authorization in the Legal Framework of the Nicaraguan Electricity Sector? - Izaba Ruíz, Carlos Ricardo (Scientific journal of social studies, 2023)
Law 272, the Electric Industry Law, de-published electricity generation, previously reserved to the State as a public service, turning it into a private activity and subjecting it to market dynamics. However, to develop the production of electricity, Law 272 establishes the generation license as a prior authorization, which operates as an entry barrier into the electricity generation market. This article addresses the issue of the authorization regime for electricity generation, as an unpublished activity, in the context of the electricity industry, as a network industry, in which the freedom of enterprise, private initiative, and free competition already meet objective limitations, to raise the need to admit only those authorizations that conform to the principles of necessity and proportionality, with a view to the Public Administration being able to protect the general interests entrusted to it, while respecting the freedom of enterprise and private initiative, necessary for the creation of a competitive generation market. Resorting to the exposition of doctrinal guidelines, as well as the comparative law of countries such as Spain, Guatemala, and Chile, this article questions the need for a generation license and proposes a lege ferenda reform that institutes free electricity generation. For the investigation, use has been made mainly of the systemic method by which the contradiction between an unpublished generation and its subjection to the generation license is sustained.
Keywords: Administrative concession; authorization; depublishing administrative; generation license